Rereading Surah al-Nisa’ [4]: 34: Muḥammad Ḥusayn Faḍl Allāh’s Contextual Approach to Gender Equality in Islam - Yuwafi, AH. Syukron; Ghorbanali Karimzadeh Gharamaleki (Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2023)
The discourse on gender equality in Islam often sparks theological debates, particularly regarding the interpretation of Surah al-Nisā’ [4]: 34, which is frequently used to justify male superiority over women. This article critically examines Muḥammad Ḥusayn Faḍl Allāh’s (1935–2010) interpretation of this verse in his Tafsīr min Waḥy al-Qur’ān. The study addresses two questions: how Faḍl Allāh interprets qiwāmah, and how his thinking on gender equality is constructed. Using a qualitative approach with literature review, the study finds that Faḍl Allāh interprets qiwāmah contextually and functionally within husband-wife relations, rather than as a justification for male dominance. The construction of his thought that is based on historical-conceptual interpretation, leads to the concept of substantive justice and moral responsibility. Faḍl Allāh’s rejection of interpretations that justify violence or the subjugation of women is unequivocal, and he positions gender equality as the paramount ethical ideal of Islam, placing significant emphasis on the well-being of families and society as a whole. This finding shows the urgency of a progressive and responsive interpretive approach to gender issues, especially in the context of rereading religious texts.